Values-Based Physical Education and Teacher Education in South Africa - Cherese Farrah Jones; CJ Rouw (African Journal of Teacher Education, 2022)
This qualitative research presents PE (Physical Education) teacher training workshops (TTW) which were developed and evaluated through the teachers’ feedback and reflections. Its goal was to create a PE programme enriched with the values of Olympism and Ubuntuism based on the idea that values-based education offers an investment in individual and societal improvement by implementing a values framework. Participatory action research was used to determine how data was collected, analysed, and presented on an ongoing, cyclical basis. The theoretical perspectives of the experiential learning theory and the cooperative learning theory were applied to teaching PE during the in-service physical education TTW. Ten PE teachers from five schools in the Tshwane District of South Africa participated as they best informed the research question and enhanced their understanding of the phenomenon under study.